PELATIHAN BAHASA INGGRIS BAGI GURU-GURU SMA BOPKRI 1 YOGYAKARTA: BELAJAR TIDAK MENGENAL BATAS USIA - Adaninggar Septi Subekti; Andreas Winardi; Mega Wati; Anesti Budi Ermerawati; Lemmuela Alvita Kurniawati; Ignatius Tri Endarto; Arida Susyetina; Fransisca Endang Lestariningsih (Universitas Muhammadiyah Tapanuli Selatan, 2022)
The community service programme was conducted in the form of a training on Basic English for teachers of SMA Bopkri 1 Yogyakarta. The training was conducted online through the Zoom platform and offline at the school. It was divided into ten sessions in the course of two months from 17 February 2022 up to 21 April 2022. Fifteen teachers participated in the training. The materials were understanding sermons, greetings and introduction, describing school facilities, doing school tours, describing school culture, hospitality, entertaining guests, doing small talks, and celebration of learning. The training was conducted in response to the need of the school to improve the English skills of the participants as the school had biweekly English sermons and the probability of having foreign guests. Generally, the training was a success and most of the participants who were adult learners and senior teachers with decades of teaching experiences demonstrated high motivation to learn despite the challenges. The use of three languages: Indonesian, Javanese, and English and the minimum use of technological tools were found to positively affect the participants’ motivation and learning in general. Flexibility in instructional process and relevance of materials were also key factors for success.